Nanostructure Nickel-Based Selenides as Cathode Materials for Hybrid Battery-Supercapacitors - Sun, Haocheng; Wang, Chensheng; Qi, Zhiqiang; Hu, Wenliang; Zhang, Zhijie (Frontiers in Chemistry, 2021)
Supercapacitors (BSCs) have attracted many attentions and already became part of some high power derived devices such as Tesla's electric cars because of their higher power density. Among all types of electrical energy storage devices, battery supercapacitors are the most promising for superior performance characteristics, including short charging time, high power density, safety, easy fabrication procedures, and long operational life. An SC usually consists of two foremost components, namely electrode materials, and electrolyte. The selection of appropriate electrode materials with rational nanostructured designs have resulted in improved electrochemical properties for high performance and has reduced the cost of SCs. In this review, we mainly spotlight the nickel-based selenides nanostructured which applied as high-performance cathode materials for SCs. Different nickel-based selenides materials are highlighted in various categories, such as nickel-cobalt-based bimetallic chalcogenides and nickel-M based selenides. Also, we mentioned material modification for this material type. Finally, the designing strategy and future improvements on nickel-based selenides materials for the application of SCs are also discussed.